A multifrequency ALMA characterization of substructures in the GM Aur protoplanetary disk - Huang, Jane; Andrews, Sean M.; Dullemond, Cornelis; Öberg, Karin I.; Qi, Chunhua; Zhu, Zhaohuan; Birnstiel, Tilman; Carpenter, John M.; Isella, Andrea; Macías, Enrique; McClure, Melissa K.; Pérez, Laura M.; et al. (The astrophysical journal, 2020)
The protoplanetary disk around the T Tauri star GM Aur was one of the first hypothesized to be in the midst of being cleared out by a forming planet. As a result, GM Aur has had an outsized influence on our understanding of disk structure and evolution. We present 1.1 and 2.1 mm ALMA continuum observations of the GM Aur disk at a resolution of ∼50 mas (∼8 au), as well as HCO+ J = 3 − 2 observations at a resolution of ∼100 mas. The dust continuum shows at least three rings atop faint, extended emission. Unresolved emission is detected at the center of the disk cavity at both wavelengths, likely due to a combination of dust and free-free emission. Compared to the 1.1 mm image, the 2.1 mm image shows a more pronounced “shoulder” near R ∼ 40 au, highlighting the utility of longer-wavelength observations for characterizing disk substructures. The spectral index α features strong radial variations, with minima near the emission peaks and maxima near the gaps. While low spectral indices have often been ascribed to grain growth and dust trapping, the optical depth of GM Aur’s inner two emission rings renders their dust properties ambiguous. The gaps and outer disk (R > 100 au) are optically thin at both wavelengths. Meanwhile, the HCO+ emission indicates that the gas cavity is more compact than the dust cavity traced by the millimeter continuum, similar to other disks traditionally classified as “transitional.”
Gesehen am 28.10.2020